Job insecure Due to AI: Work Engagement and Roles of Person-Job Fitness, Person-Supervisor Fitness, and Person-Organization Fitness - Hahm, Sangwoo; Rhee, Hongyeon (International Journal of Psychosocial Rehabilitation, 2020)
The development of Information Technology and the shift to the Fourth Industrial Revolution has brought rapid changes to enterprises and workers. This rapid change has caused uncertainty and instability in the work environment. As a result, people are faced with the challenge of adapting to rapid changes and creating new values. This research focuses on the development of information technology and the shift to the fourth industrial revolution and the need to reduce the negative effects that will arise from the increase of other uncertainties and instabilities and of these factors. This paper explains the role of person-job fitness, person-supervisor fitness, and person-organization fitness as a way to increase the work engagement of workers in a changing environment. As these diverse adaptations increase, workers will experience less instability and uncertainty even though the environment changes. This effect will improve enthusiasm for business. Thus, by increasing the diversity of workers’ adaptability, workers will be able to work better in the rapidly changing fourth industrial revolution ara